PERAN STRATEGI MILITER DAN MANUVER POLITIK DALAM SERANGAN UMUM 1 MARET 1949 DI YOGYAKARTA - Fitrianto, Ega Millenio; Lestari, Emi Tipuk (Universitas Negeri Surabaya, 2025)
The General Offensive of March 1, 1949, in Yogyakarta has often been portrayed primarily as a military achievement within Indonesia’s War of Independence. However, such interpretations tend to overlook its broader political function and strategic intent within the international diplomatic arena. This study aims to critically examine the General Offensive of March 1, 1949, as an integrated military–political strategy designed not merely to reclaim territory, but to counter Dutch claims of Republican collapse and to influence international opinion. Employing the historical method, this research is based on an in-depth analysis of archival documents, contemporary newspapers, military reports, and relevant secondary literature. A descriptive–analytical qualitative approach is used to compare Indonesian and Dutch narratives and to assess the interaction between military operations and political objectives. The findings demonstrate that the effectiveness of the General Offensive lay less in its temporary territorial control than in its symbolic and communicative impact. The operation functioned as a deliberate political signal aimed at international observers, reinforcing the continued existence and operational capacity of the Republic of Indonesia while undermining Dutch diplomatic narratives. This study argues that the General Offensive of March 1, 1949, should be understood as a strategic convergence of military action and political maneuvering rather than as a purely tactical success. By situating the offensive within its diplomatic and historiographical context, the article contributes to a more nuanced understanding of Indonesian military history and highlights the importance of political objectives in revolutionary warfare.